Vilnius, which did not become the capital of West Belarus - Boćkowski, Daniel (Genocidas ir rezistencija, 2009)
The article deals with the problem of the State dependence of Vilnius on the eve and at the beginning of World War II (August–October 1939). The problem of Vilnius is considered within the broad context of international relations in Europe. Special attention is devoted to the plans and actions on the eve of Poland’s onslaught and in the second half of September 1939. After the partition by Nazi Germany and the Soviet Union the spheres of influence of Poland and the Baltic States, the question of occupation and annexation of the eastern lands of Poland (Western Ukraine, Western Belarus and Vilnius Territory) came forth. The Soviets planned to settle that issue by staging the independent accession of the occupied territories to the Soviet Union. Nevertheless, the settlement of the issue of Vilnius was far more complicated than the incorporation of the eastern lands of Poland. Even in the secret protocols of the Molotov–Ribbentrop Pact it was foreseen to take into account the interests of Lithuania in the Vilnius Territory. J. Stalin used Vilnius as the means of pressure on Lithuania seeking to sign the agreement of mutual assistance and to dislocate the Soviet military bases in Lithuania. The Soviets threatened to annex the Vilnius Territory to the Byelorussian SSR in the case Lithuania refused to allow the stationing of the Soviet military bases. Vilnius became a certain Trojan horse, which opened the gates to the subjugation of Lithuania and other Baltic States.